The Future Implementation of Automation and AI In Smart Logistics (Journal of Finance, Business and Management Studies, 2022)
Augmenting application areas and depths of autonomous systems in logistics provide a new level of challenge for the analysis and design of human and machine synergy concepts. The advancements in the technologies, the ramification to modify the operation in the transportation, warehousing and the revolution in the business procedures as the result of the accumulating orders along with the complications involved in it, and the shortage in the management skills as like it allows us to save time, money and manpower because it helps in automating various time-consuming processes and helps in demand forecasting. This is essential for the design of a variety of automated logistics systems, including autonomous driving supervision for drivers and pilots. Smart Logistics can be implemented by using the technological concepts of Information and Communication Technologies (ICT), the internet of things (IoT), cyber-physical system (CPS), and the physical internet (PI). The relevance of the artificial intelligence in the warehousing and transportation to make it a smart environment for the automated logistics has been proposed in this paper. Apart from that The paper also concentrates on the automated storage, delivery and the retrieval using the internet of things (IoT), and artificial intelligence to have access to make things easier.